2017
DOI: 10.1002/tox.22443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ochratoxin A on ER stress, MAPK signaling pathway and autophagy of kidney and spleen in pigs

Abstract: Ochratoxin A (OTA), a worldwide mycotoxin found in food and feeds, is a potent nephrotoxin and immunotoxin in animals and humans. This research was conducted to evaluate whether endoplasmic reticulum (ER) stress, MAPK signaling pathway and autophagy were induced by OTA in kidney and spleen of pigs. Twenty-seven crossbred pigs randomly allocated to 3 groups were fed for 42 days ad libitum a basal diet without (Con group, 0.00 μg OTA/kg) and with supplementation of OTA at 400 (OTA-L group) and 800 μg/kg (OTA-H g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Nrf2, which is a major transcription factor in the antioxidant system and is involved in the regulation of antioxidant enzyme expression, is inhibited by Keap1 under physiological conditions [34,35]. Previous studies have shown that OTA toxicity is associated with oxidative stress [36], apoptosis [37], autophagic cell death [38], mitochondrial dysfunction and induction of mitochondrial biogenesis [39]. Studies have indicated that oxidative stress is a key determinant of OTA-induced toxicity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, which is a major transcription factor in the antioxidant system and is involved in the regulation of antioxidant enzyme expression, is inhibited by Keap1 under physiological conditions [34,35]. Previous studies have shown that OTA toxicity is associated with oxidative stress [36], apoptosis [37], autophagic cell death [38], mitochondrial dysfunction and induction of mitochondrial biogenesis [39]. Studies have indicated that oxidative stress is a key determinant of OTA-induced toxicity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving mammalian species in vitro (Bhat et al, 2016;Gayathri et al, 2015;Lautert et al, 2014; and in vivo (Aydin et al, 2003;Tanaka et al, 2016) showed nephrotoxic, hepatotoxic, immunotoxic, enterotoxic, neurotoxic and teratogenic effects of OTA. The toxicity and carcinogenic mechanisms of OTA have been associated with induction of oxidative stress (Costa et al, 2016), cell apoptosis (Ramyaa and Padma, 2013), cell autophagy/mitophagy (Gan et al, 2017;Qian et al, 2017) and protein synthesis inhibition (Mally and Dekant, 2009).…”
Section: Ochratoxin Amentioning
confidence: 99%
“…ROS generation has been reported to trigger OTA toxicity (Zhu et al, 2017). Several oxidative stress mechanisms elicited by OTA have been proposed through in vivo (Abdel-Wahhab et al, 2017;Gan et al, 2017) and in vitro studies (Bhat et al, 2016;Ramyaa et al, 2014) (Figure 1). OTA can cause damage due to oxidative stress through the generation of hydroxyl radicals via the Fenton reaction, via flavoprotein NADPH-cytochrome P450 activation and inhibition of Nrf2 activation and gene transcription.…”
Section: Ochratoxin Amentioning
confidence: 99%
“…However, practice of CsA is restricted because of its side effects on heart, liver, and nervous system. The target organ of OTA is also kidney and several studies showed that OTA could cause renal injury in cells and animals 20,29 . And the dosage in our study is 0.25 mg/kg per day, which is nontoxic for mice.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of transforming growth factor-beta1 (TGF-β1), excessive apoptosis, autophagy, and production of inflammatory factors could be upregulated in chronic CsA nephropathy 18 . OTA-induced nephropathy was related to them as well [19][20][21] . Among them, inflammation plays a vital role in the progression of renal diseases, in which toll-like receptor 4 (TLR4) represents a major component in innate immunity.…”
Section: Introductionmentioning
confidence: 88%